2012
DOI: 10.1024/0036-7281/a000320
|View full text |Cite
|
Sign up to set email alerts
|

New World camelids and Bovine Virus Diarrhea Virus (BVDV) infection in Switzerland

Abstract: The aim of this study was the search for persistently infected (PI) New World camelids 13 (NWC) as a possible source of Bovine Virus Diarrhea Virus (BVDV) infection for other 14 NWC or cattle in Switzerland, where an eradication programm for BVDV has been 15 implemented. Different organs from 166 animals and 101 sera from different parts of 16 Switzerland were tested for BVDV antigen by means of immunohistochemistry and 17 HerdChek*BVDV Ag/Serum Plus. None of the organs and sera was found to be 18 positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Dysregulation of RAS genes has been associated with ERMS 31. Elevated expression of MET has also been associated with more advanced disease 32,33. Recent studies have also demonstrated that elevated messenger RNA levels, and protein expression of ALK have been associated with ARMS and worse clinical outcome 34,35.…”
Section: Rms Pathology and Tumor Biologymentioning
confidence: 99%
“…Dysregulation of RAS genes has been associated with ERMS 31. Elevated expression of MET has also been associated with more advanced disease 32,33. Recent studies have also demonstrated that elevated messenger RNA levels, and protein expression of ALK have been associated with ARMS and worse clinical outcome 34,35.…”
Section: Rms Pathology and Tumor Biologymentioning
confidence: 99%